2013
DOI: 10.1590/s0103-51502013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Ensino e práticas da fisioterapia aplicada à criança na formação do fisioterapeuta

Abstract: INTRODUÇÃO: É um dos desafios delegados aos docentes da Fisioterapia formar profissionais conhecedores do que é particular na abordagem à criança, no intuito de favorecer estratégias ambientais e sociais favoráveis ao desenvolvimento potencial da criança. OBJETIVO: Investigar o ensino e a aprendizagem da Fisioterapia aplicada à criança, nos cursos de Fisioterapia de Alagoas. MÉTODOS E MATERIAIS: Estudo exploratório, descritivo, construído a partir de uma abordagem qualitativa e quantitativa, realizado com doce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…Previous studies have shown that the active methodology has been well accepted in Physical therapy courses, when approaching contents related to the understanding of the health-illness process [6,15] and the results suggest teaching practices that favor a dialogued and critical education [2,3,22]. However, little evidence shows the TBL method more specifically for this undergraduate course.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Previous studies have shown that the active methodology has been well accepted in Physical therapy courses, when approaching contents related to the understanding of the health-illness process [6,15] and the results suggest teaching practices that favor a dialogued and critical education [2,3,22]. However, little evidence shows the TBL method more specifically for this undergraduate course.…”
Section: Discussionmentioning
confidence: 81%
“…The active methodology requires knowledge and abilities from the professor that go beyond the diversity of teaching techniques. Guedes et al [6] observed that professors that teach Physical therapy practices applied to children used a great variety of instructional resources, such as multimedia, dolls, dynamics, work presentation, practical lessons, curricular internship and clinical case discussions. However, predominantly they observed a focus on the traditional methodology, mainly transmissive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schreiber et al 12 found that although 70% of the institutions studied indicated that the number of existing sites for pediatric clinical practice met the curricular needs, only 7% of the programs made experience mandatory. Guedes et al 13 point out that the teaching of pediatric physiotherapy follows disease-oriented practices, and recommend the introduction of new contents and increase the workload of disciplines focused on pediatrics, as well as improving the theoretical-practical articulation and creating physical spaces for this practice.…”
Section: A Theoretical Preamble: the Stigma Of Chronicity In Childrenmentioning
confidence: 99%